African American Race Is Associated With Poorer Outcomes in Heart Failure Patients. (April 2017) - Wierenga, Kelly L.; Dekker, Rebecca L.; Lennie, Terry A.; Chung, Misook L.; Dracup, Kathleen
Health care disparities associated with African American race may influence event-free survival in patients with heart failure (HF). A secondary data analysis included 863 outpatients enrolled in a multicenter HF registry. Cox regression was used to determine whether African American race was associated with shorter HF event-free survival after controlling for covariates. The multivariable-adjusted hazard ratios (95% confidence intervals [CI]) of older age (1.03, 95% CI = [1.01, 1.04]), New York Heart Association (NYHA) functional class (1.73, 95% CI = [1.29, 2.31]), depressive symptoms (1.05, 95% CI = [1.02, 1.07]), and African American race (1.64, 95% CI = [1.01, 2.68]) were predictors of shorter event-free survival (all p s < .05). Comparisons showed that NYHA functional class was predictive of shorter event-free survival in Caucasians (1.81, 95% CI = [1.33, 2.46]) but not in African Americans (1.24, 95% CI = [.40, 3.81]). African Americans with HF experienced a disparate risk of shorter event-free survival not explained by a variety of risk factors.